Child feeding perceptions among mothers with eating disorders. (1st December 2015) - Sadeh-Sharvit, Shiri; Levy-Shiff, Rachel; Feldman, Talya; Ram, Anca; Gur, Eitan; Zubery, Eynat; Steiner, Evelyne; Latzer, Yael; Lock, James D.
Abstract: Feeding and eating difficulties are documented among the offspring of mothers with eating disorders. Understanding the perspective of mothers with eating disorders is likely essential to develop parent-based early prevention programs for children of these mothers. In the present study, twenty-nine mothers who were diagnosed with an eating disorder prior to becoming mothers and who currently had toddler age children participated in a semi-structured interview examining maternal functioning and child feeding. The maternal perceptions that emerged from the interviews were sorted into central themes and subcategories using interpretive phenomenological analysis. Data indicate that mothers with eating disorders express preoccupation with their child's eating, shape and weight, and many dilemmas about child feeding. They also reported rarity of family meals and their toddlers' preliminary awareness of maternal symptoms. Maternal concerns regarding child nutrition, feeding and weight were reported as more intense in regards to daughters. These maternal perceptions illuminate the maternal psychological processes that underlie the feeding and eating problems of the children of mothers with lifetime eating disorders. Findings should be addressed in the evaluation, treatment, and research of adult and childhood eating disorders. Highlights: Mothers with eating disorders limited toddlers' intake and exploration of food. The mothers tended to eat different meals at a different time from their children. Mothers reported more food restriction, control and comments with their daughters. Mothers stated their toddlers were aware of maternal symptoms and imitated them. Maternal prenatal eating disorders compromise healthy feeding decisions.